2021
DOI: 10.1002/saj2.20251
|View full text |Cite
|
Sign up to set email alerts
|

Compost applications increase bacterial community diversity in the apple rhizosphere

Abstract: Sustainable practices are key to the improvement of soil fertility and quality in apple (Malus × domestica Borkh.) orchards. Rootstock genotype and fertilizer inputs can alter soil biology, as well as aboveground traits including nutrient acquisition. In this study, a factorial design was used to assess the interaction between two apple rootstocks, 'Geneva 41' ('G.41') and 'Malling 9' ('M.9') with four fertilizer treatments [chicken-litter compost, yardwaste compost, fertigation using Ca(NO 3 ) 2 , and an unam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 93 publications
2
12
1
Order By: Relevance
“…In this research, PCoA revealed that bacterial community composition had significant differences among the six fertilization treatments. Studies have shown that long-term application of organic fertilizers can promote microbial species richness and improve soil nutrient utilization efficiency (Sharaf et al, 2021). The application of organic fertilizer associated with microbial richness increased as Proteobacteria ,Gemmatimonadetes , and Cyanobacteria increased (Fig.…”
Section: Effects Of Soil Chemical Properties On the Rhizosphere Bacte...mentioning
confidence: 96%
“…In this research, PCoA revealed that bacterial community composition had significant differences among the six fertilization treatments. Studies have shown that long-term application of organic fertilizers can promote microbial species richness and improve soil nutrient utilization efficiency (Sharaf et al, 2021). The application of organic fertilizer associated with microbial richness increased as Proteobacteria ,Gemmatimonadetes , and Cyanobacteria increased (Fig.…”
Section: Effects Of Soil Chemical Properties On the Rhizosphere Bacte...mentioning
confidence: 96%
“…The rootstock genotype cannot only modulate horticultural traits such as tree size and productivity [ 10 ] but can also influence the composition of the rhizosphere microbial communities [ 2 ]. The genotype influence on the rhizobiome can even extend to within-species differences as demonstrated in grapes [ 11 14 ], apples [ 15 17 ], tomatoes [ 18 ], and Populus sp. [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Application of compost can also impact the soil microbiome and increase microbial diversity [ 51 , 52 ], which has been linked to reduced disease incidence [ 53 , 54 ]. A recent study showed that compost application increased the bacterial diversity in the apple rhizosphere of two rootstocks, and that interactions between compost and rootstocks controlled variations in the rhizobiome composition that may determine increases in tree biomass [ 17 ]. However, the interaction between compost and rootstocks in the citrus rhizobiome has not been explored, nor has the relationship between rhizobiome taxa and root nutrient concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It starts with keeping our soils healthy. Sustainable soil management practices (e.g., minimizing disturbance and adding compost and manure as well as living mulches with grass, legumes, or forbs) have been shown to build healthy soils and improve soil fertility in apple orchards (Neilsen et al., 2014; Sharaf et al., 2021).…”
mentioning
confidence: 99%
“…Soil chemical properties can determine nutrient retention and availability, pH (acidity/alkalinity), salinity, and the presence of any contaminants (e.g., heavy metals, herbicides, and pesticide residues). Active soil biological communities (e.g., bacteria, nematodes, and fungi) can interact with the root systems in the rhizosphere, convert nutrients into plant‐available forms, and compete with plant pathogens (Sharaf et al., 2021). Hence, improving our understanding of physical, chemical, and biological soil health is essential to maximize apple production with no environmental impact.…”
mentioning
confidence: 99%